P247 Understanding patient perspectives on dysplasia cancer risk and its management. (25th January 2019) - Kabir, M; Thomas-Gibson, S; Hart, A; Faiz, O; Warusavitarne, J; Wilson, A
Abstract: Background: Uncertainty in inflammatory bowel disease (IBD) dysplasia prognosis makes management decision-making challenging. Further understanding of patient preferences is required to help clinicians support this process. Methods: A web survey, evaluating views on dysplasia, was administered via IBD charity social media in November 2018, to UK IBD patients who have had colorectal cancer (CRC) surveillance. Validated scores assessed whether their decisions were influenced by concerns about developing CRC (Cancer Worry Scale, CWS), their dispositional optimism (revised Life Orientation Test, LOT-R), numerical ability (Subjective Numeracy Scale, SNS) and health-related quality of life (Short IBD Questionnaire, SIBDQ). Results: There were 50 respondents (see Table 1). Being told that a dysplastic lesion was 'high risk' or 'low risk' in words, corresponded with a mean perceived risk of 56% and 17%, respectively. Of the patients who were dysplasia-naïve ( n = 29), the mean CRC risk would have to be 50% in order for them to accept colectomy. Pain, lack of bowel control and inability to do things they enjoyed were the top-most concerns in >70%. If they were told that they had unresectable dysplasia, 34% would choose to have a colectomy and 28% would choose frequent surveillance instead. Those who preferred colectomy were significantly more likely to be employed or a full-time carer (80% vs. 25%; p = 0.02), were more likely to believe that dysplasia progressed to CRC within a year (50% vs. 0%; p = 0.02) and that the words 'high risk' meant that their mean CRC risk was 70%, whereas those preferring surveillance perceived 'high risk' to be a mean of 47% ( p = 0.01). Of the patients with prior dysplasia diagnoses ( n = 21), 90% were first told by a gastroenterologist. A substantial minority did not feel well informed about the risk of CRC (24%) and the management of dysplasia (29%). Fifty-five per cent felt their relationship with their doctor in the final management decision-making process was equal but 45% did not. Sixty-seven per cent chose to have a colectomy. Those who remained on surveillance listed lack of symptoms and concerns about requiring a stoma or developing complications as deterrent factors for surgery. There was no significant mean difference in LOT-R, SNS, SIBDQ, CWS or Decision Regret Scale scores between all subset groups. Conclusions: This survey has suggested that about a quarter of IBD dysplasia patients did not feel well informed about their cancer risks and management. Further qualitative work is required to understand how best to support shared decision-making in IBD dysplasia.